Aplicação do Protocolo Certifica: certificação orgânica na Associação de Produtores da Comunidade de Campo Limpo – Santo Antônio do Tauá - GONÇALVES, Bruno Santos (2021)
The project aimed to apply and develop the Certifica Protocol to products marketed by the Rural Producers Association of the Campo Limpo Community (APROCAMP), in the municipality of Santa Antônio do Tauá, Pará. A semi-structured questionnaire and a visit to field in 02 production units. At APROCAMP, the production system is diversified, the main activities that generate income are priprioca, storax, pataqueira and vegetables. The application of the Certifica Protocol was guided by the certification management, through the reality of the association's process and production. The development included the effective management of the Certifica Protocol and the authorization of the Organic Certification of the association's products, including organic products: vegetables, legumes, fruits and aromatic plants. Producers participating in the project accepted the development and implementation of the Certifica Protocol in order to add value to APROCAMP's management, operation and market; thus, being a reference in this first management model through the protocol. The management and development of the protocol was validated through questionnaires with indicators divided by organizational, operational and sustainability dimensions, completed by the members of the association, with an average approval rate of 83 to 93%. Enabling the Certifica Protocol as a management tool for rural producers, cooperatives and associations to independently develop the organic certification process; consequently, opening doors to the international market and further promoting the national and regional market.